Strategi Bisnis KSPPS Nuri Jatim dalam Memasyarakatkan Ekonomi Syariah di Jawa Timur. - Khotibul Umam; Ach. Sudis Alwi (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to analyze the business strategy of KSPPS Nuri Jatim in Socializing the Islamic Economy in East Java. Data analysis in this study consisted of data exploration, data reduction, validity test with data triangulation and drawing conclusions. Based on the results of the analysis of strengths, weaknesses, opportunities and threats, it shows several strategies that can be carried out by KSPPS Nuri Jatim in disseminating sharia economics in East Java, namely (1) SO Strategy, by increasing sharia economic promotion activities to increase sharia financial literacy, increasing cooperation with stakeholders in the development of the sharia economy and optimizing the use of information technology in disseminating the sharia economy, (2) the ST strategy, namely by massively socializing the existence of KSPPS Nuri Jatim, determining a more competitive margin strategy including profit sharing rates, and increasing the socialization of the prohibition of bank interest by MUI, (3) the WO strategy, namely by analyzing positions and employee needs, providing training to improve the quality of human resources and optimizing the use of technology for sharia financial transaction service activities, and (4) WT strategy which includes product innovation varied, cooperate with external training institutions and pay more attention to service quality.